New Porous Heterostructures Based on Organo-Modified Graphene Oxide for CO2 Capture - Thomou, Eleni; Diamanti, Evmorfia K.; Enotiadis, Apostolos; Spyrou, Konstantinos; Mitsari, Efstratia; Boutsika, Lamprini G.; Sapalidis, Andreas; Moretón Alfonsín, Estela; De Luca, Oreste; Gournis, Dimitrios; Rudolf, Petra (Frontiers in Chemistry, 2020)
In this work, we report on a facile and rapid synthetic procedure to create highly porous heterostructures with tailored properties through the silylation of organically modified graphene oxide. Three silica precursors with various structural characteristics (comprising alkyl or phenyl groups) were employed to create high-yield silica networks as pillars between the organo-modified graphene oxide layers. The removal of organic molecules through the thermal decomposition generates porous heterostructures with very high surface areas (≥ 500 m2/g), which are very attractive for potential use in diverse applications such as catalysis, absorption and as fillers in polymer nanocomposites. The final hybrid products were characterized by X-ray diffraction, Fourier transform infrared and X-ray photoelectron spectroscopies, thermogravimetric analysis, scanning electron microscopy and porosity measurements. As proof of principle, the porous heterostructure with the maximum surface area was chosen for investigating its CO2 adsorption properties.